An in silico perception for newly isolated flavonoids from peach fruit as privileged avenue for a countermeasure outbreak of COVID-19. Issue 50 (13th August 2020) - Allam, Ahmed E.; Assaf, Hamdy K.; Hassan, Heba Ali; Shimizu, Kuniyoshi; Elshaier, Yaseen A. M. M.
Abstract : 3′-Hydroxy-4′-methoxy-chroman-7- O -β-d -glucopyranoside 4, together with three known compounds, ferulic acid heptyl ester 1, naringenin 2, and 4, 2′, 4′-trihydroxy-6′-methoxychalcone-4′- O -β-d -glucopyranoside 3, was isolated from peach fruits. Abstract : 3′-Hydroxy-4′-methoxy-chroman-7- O -β-d -glucopyranoside 4 was first isolated from a natural source, together with three known compounds, the ferulic acid heptyl ester 1, naringenin 2, and 4, 2′, 4′-trihydroxy-6′-methoxychalcone-4′- O -β-d -glucopyranoside 3, which were isolated from peach [ Prunus persica (L.) Batsch] fruits. These compounds were subjected to different virtual screening strategies in order to examine their activity to combat the COVID-19 outbreak. The study design composed of some major aspects: (a) docking with main protease (M pro ), (b) docking with spike protein, (c) 3D shape similarity study (Rapid Overlay Chemical Similarity-ROCS) to the clinically used drugs in COVID-19 patients, and finally, (d) the rule of five and the estimated pre-ADMT properties of the separated flavonoids. Docking study with M pro of SARS-CoV-2 (PDB ID:; 6LU7, and ; 6Y2F ) showed that compound 3, its aglycone part, and compound 4 have a strong binding mode to a protease receptor with key amino acids, especially Gln:166AA, and having a similar docking pose to co-crystalized ligands. Docking with the spike protein of SARS-CoV-2 illustrated that compounds 3 and 4 have a good binding affinity to PDB ID:; 6VSB through the formation of HBs with Asp:; 467A and Asn:; 422A . According to ROCS analysis, compounds 1, 3, and 4 displayed high similarities to drugs that prevent SARS-Co2 entry to the lung cells or block the inflammatory storm causing lung injury. Compounds 3 and 4 are good candidates for drug development especially because they showed predicted activity against SARS-CoV-2 through different mechanisms either by preventing genome replication or by blocking inflammatory storm that trigger lung injury. These compounds were isolated from peach fruit, and the study supports data and continues with the recommendation of peach fruits in controlling and managing COVID-19 cases.